2019
DOI: 10.1111/jcmm.14637
|View full text |Cite
|
Sign up to set email alerts
|

Sodium hydrosulphide restores tumour necrosis factor‐α‐induced mitochondrial dysfunction and metabolic dysregulation in HL‐1 cells

Abstract: Tumour necrosis factor (TNF)‐α induces cardiac metabolic disorder and mitochondrial dysfunction. Hydrogen sulphide (H2S) contains anti‐inflammatory and biological effects in cardiomyocytes. This study investigated whether H2S modulates TNF‐α‐dysregulated mitochondrial function and metabolism in cardiomyocytes. HL‐1 cells were incubated with TNF‐α (25 ng/mL) with or without sodium hydrosulphide (NaHS, 0.1 mmol/L) for 24 hours. Cardiac peroxisome proliferator‐activated receptor (PPAR) isoforms, pro‐inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…It is worth noting that even in myocardium with impaired glucose metabolism, oxidative stress and related structural remodelling are the basis of abnormal electrical activity. H 2 S improves mitochondrial oxidative stress, respiratory dysfunction, and reduces apoptosis in HL-1 cells caused by glucose metabolism disorder, and in turn can improve atrial function in mice ( Garcia et al, 2017 ; Lee et al, 2019 ). This has similar effects to reducing oxidative stress to inhibit HL-1 cell apoptosis and improve left atrial structural remodelling induced by AF in mice ( Johnston et al, 1990 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that even in myocardium with impaired glucose metabolism, oxidative stress and related structural remodelling are the basis of abnormal electrical activity. H 2 S improves mitochondrial oxidative stress, respiratory dysfunction, and reduces apoptosis in HL-1 cells caused by glucose metabolism disorder, and in turn can improve atrial function in mice ( Garcia et al, 2017 ; Lee et al, 2019 ). This has similar effects to reducing oxidative stress to inhibit HL-1 cell apoptosis and improve left atrial structural remodelling induced by AF in mice ( Johnston et al, 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ang II + NaHS group: HL-1 cells were pre-incubated with NaHS (100 μM) for 24 h, and then treated with Ang-II for another 24 h ( Lee et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…In TNFα-stimulated mouse cardiac muscle cells, sodium hydrosulfide ameliorated the impaired mitochondrial respiration and ATP production/synthesis, and attenuated excess oxidative stress, which might be due to the enhanced expression of metabolic indices such as CPT1. The study indicated the therapeutic potential of sodium hydrosulfide for inflammation-associated cardiac dysfunctions ( Lee et al, 2019 ).…”
Section: Implications Of Carnitine Palmitoyltransferase System In Inflammatory Diseases and Cancersmentioning
confidence: 99%
“…72 The authors showed that activation of AMPK can mediate the transport of fatty acids into mitochondria through phosphorylation and inhibition of acetyl-CoA carboxylase (ACC), an important enzyme that inhibits the fatty acid oxidation, AMPK therefore enhanced the oxidation of fatty acids in HL-1 cardiomyocyte cells. 73 The same group reported that the expression of PPAR-α and PPAR-δ, transcription factors that regulate fatty acid oxidation, is decreased when cells are exposed to TNF-α. 73 TNF-α decreased carnitine O-palmitoyltransferase 1 (CPT-1) expression, which is required for the translocation of long-chain fatty acids into the mitochondrial matrix (a limiting step in beta-oxidation).…”
Section: Role Of Ifn-γ and Tnf-α In Mitochondrial Damagementioning
confidence: 99%